Moving forward: a cross sectional baseline study of staff and student attitudes towards a totally smoke free university campus - Burns, Sharyn; Jancey, Jonine; Bowser, Nicole; Comfort, Jude; Crawford, Gemma; Hallett, Jonathan; Shields, Bree; Portsmouth, Linda (BioMed Central Ltd, 2013)
Background: Baseline data were collected to inform the adoption, implementation and institutionalisation phases of a completely smoke free campus policy at a large Western Australian university with a diverse student and staff community. Methods: An online survey was randomly emailed to staff and students to measure the attitudes towards and the acceptability and enforcement of the policy prior to implementation. In total, 969 respondents completed the survey. Results: General attitudes towards smoking were negative. While smokers, ex-smokers and non-smokers were supportive of smoke free policy on campus, 65.7% of respondents felt the campus should be completely smoke free. Respondents indicated a smoke free policy should be stringently enforced. The majority of respondents reported that they had been exposed to second-hand smoke on campus (n = 768; 79.5%). Conclusion: Theory of Organisational Change provides a useful framework to support the implementation of the completely smoke free policy in the University setting. The implementation process needs to consider the broad range of issues associated with implementing a completely smoke free policy and address issues such as safety of smokers, ensuring smokers are not marginalised and ensuring a comprehensive program is implemented. These baseline findings can be used to advocate for the implementation of a comprehensive range of strategies that recognise the addictive nature of tobacco smoking and address attitude and behaviour change, environmental adaptations and effective implementation of the policy. Administration should consider smokers and non-smokers when policy is implemented.